2009
DOI: 10.1002/rem.20208
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fenton's Reagent as a Disinfectant

Abstract: Several compositions of Fenton's Reagent and hydrogen peroxide alone were used to disinfect combined sewage samples from a wastewater treatment facility. The presettled samples contained suspended solids (SS) and dissolved organic carbon (DOC) at concentrations of 28 and 290 mg/L, respectively. Disinfection with Fenton's Reagent was carried out at a pH between 5.90 and 6.0 and at a temperature of 25 • C. All disinfected samples contained residual oxidants. Under all reaction conditions studied, complete inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 8 publications
1
15
0
10
Order By: Relevance
“…In the absence of a light source, hydrogen peroxide will decompose by Fe 2+ ions that present in the aqueous phase, resulting in the formation of hydroxyl radicals [33], [40], [41]. Process of generation of hydroxyl radicals by Fenton's reaction is very sensitive to pH, the ratio of Fe 2+ to H 2 O 2 and the concentration of Fe 2+ [42], [43]. Fenton's reaction is effective for acidic conditions (optimum pH of 3 -4), and its efficiency may rapidly decrease at pH above 5 [20], [43], [44].…”
Section: Fenton Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a light source, hydrogen peroxide will decompose by Fe 2+ ions that present in the aqueous phase, resulting in the formation of hydroxyl radicals [33], [40], [41]. Process of generation of hydroxyl radicals by Fenton's reaction is very sensitive to pH, the ratio of Fe 2+ to H 2 O 2 and the concentration of Fe 2+ [42], [43]. Fenton's reaction is effective for acidic conditions (optimum pH of 3 -4), and its efficiency may rapidly decrease at pH above 5 [20], [43], [44].…”
Section: Fenton Processesmentioning
confidence: 99%
“…Another advantage over chlorine-based disinfectants is the prevention of bacteria regrowth potential without formation of deleterious disinfection by-products. Chemicals involved in the Fenton's process are easily handled, are not toxic or harmful to the environment, and are economically attractive [20], [41], [42], [43]. Another advantage of the Fenton's process is that no energy input is necessary to activate hydrogen peroxide, making the reaction possible at atmospheric pressure and at room temperature [43].…”
Section: Fenton Processesmentioning
confidence: 99%
“…Conventional chemical disinfectants such as chlorine gas and hypochlorite have some advantages including rapid oxidation rates, low cost and high biocide potency. However, the mutagenic and carcinogenic by-products produced due to the application of these disinfectants have motivated scientists to seek alternative methods which may be more environmentally friendly (Liberti et al, 2000;Selvakumar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, to achieve a satisfactory level of STW disinfection, high concentrations of HP and a long detention time are required (Ragab-Depre, 1982;Selvakumar et al, 2009;Wagner et al, 2002). Wagner et al (2002) showed that to achieve a 5 log reduction of E. coli in STW, more than 700 mg L -1 of HP is required for 2 h. Velasquez et al (2008) reduced FC and pathogenic bacteria of advanced primary treatment effluent to acceptable levels according to international legislation, however, this required more than 250 mg L -1 of HP and contact times of over 2 h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation